P07.13 Detection of treponema pallidum dna from whole blood and earlobe specimens in patients from two sti clinics in lima, peru. (13th September 2015) - Chow, JY; Flores, JA; Vargas, SK; Leon, SR; Konda, KA; Klausner, JD; Caceres, CF
Abstract : Background: Prior studies have reported PCR detection of Treponema pallidum DNA from whole blood and earlobe scrapings. Factors affecting efficiency such as PCR target gene and clinical stage of syphilis have been studied. We aimed to determine other factors associated with detection of T.pallidum DNA from whole blood and earlobe samples. Methods: Data were obtained from baseline samples collected for a prospective cohort study of 401 men who have sex with men (MSM) and transgender women (TW) in Lima, Peru. Participants were assessed for HIV using rapid HIV testing (Alere Determine, USA), a combined Antigen/Antibody HIV EIA, and Western blot confirmation (Genscreen ULTRA HIV Ag-Ab and Genetic Systems HIV-1 Western Blot, Bio Rad, USA). Syphilis infection was assessed with RPR (BD Macro-Vue, USA) and TPPA (Fujirebio, Japan). Whole blood samples and earlobe capillary blood was collected from patients with a positive RPR and TPPA. DNA extraction was performed using the QIAamp mini kit (Qiagen, Valencia, CA), and samples were then concentrated. Ujchowsing specific primers for the TpN47 gene, an aliquot of the DNA sample was amplified using conventional PCR for participants with high RPR titers (≥1:16). Positivity was determined by visual detection of PCR product on 1% agarose gel. Results: 56 participants had RPR titer ≥1:16 (1:16(n = 18), 1:32(n = 16), 1:64(n = 17), 1:128(n = 3), and 1:256(n = 2)). A total of 7 (12.5%) participants had T.pallidum DNA detected from whole blood, and 6 (10.7%) from earlobe capillary blood  (10 participants total). Of these 10 participants, 5 were HIV positive, and 5 were HIV negative. Conclusion: Our relatively low efficiency of detection from both whole blood and earlobe samples suggest that neither HIV status nor high RPR titer (≥1:16) seem to predict high likelihood of DNA detection. Further study is ongoing to determine if these or other characteristics are associated with positive detection of T.pallidum DNA. Disclosure of interest statement: The Picasso study is funded by a grant from the United States NIAID and was implemented by the Universidad Peruana Cayetano Heredia in collaboration with the University of California, Los Angeles. The molecular part of the study was implemented under the supervision of the University of Washington. No pharmaceutical grants were received during the development of this study.